Traversal of arbitrary sequences of UCM symbolic transitions for test generation - Guba, A.A. (Проблеми програмування, 2014)
The paper proposes a method of traversal of high-level multi-threaded models formalized in UCM language. The pros and cons of this approach comparing to the existing ones are considered. The method that allows state space exploring of UCM models using symbolic solving and proving is presented. The generation of symbolic traces used for software system testing is described. Запропоновано метод обходу високорівневих багатопотокових моделей, які формалізовані мовою UCM. Розглядаються переваги та недоліки даного підходу у порівнянні з існуючими. Представлений метод дозволяє обходити простір станів моделей UCM, використовуючи символьне розв’язання та доведення. Описана генерація символьних трас, які використовуються для тестування програмних систем.